2020
DOI: 10.1002/jbt.22684
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective role of gallic acid in aflatoxin B1‐induced behavioral abnormalities in rats

Abstract: The neurotoxic impact of dietary exposure to aflatoxin B1 (AFB1) is documented in experimental and epidemiological studies. Gallic acid (GA) is a triphenolic phytochemical with potent anticancer, anti‐inflammatory, and antioxidant activities. There is a knowledge gap on the influence of GA on AFB1‐induced neurotoxicity. This study probed the influence of GA on neurobehavioral and biochemical abnormalities in rats orally treated with AFB1 per se (75 µg/kg body weight) or administered together with GA (20 and 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 57 publications
(56 reference statements)
4
23
0
Order By: Relevance
“…showed that AFB 1 administration induced weight loss in the present study, and this observation is consistent with previous reports (Adedara et al, 2021;Sun et al, 2018).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…showed that AFB 1 administration induced weight loss in the present study, and this observation is consistent with previous reports (Adedara et al, 2021;Sun et al, 2018).…”
Section: Discussionsupporting
confidence: 94%
“…increasing the oxidative state of the tissues. Also, the role of RNS in tissue injury has been studied (Adedara et al, 2021;Owumi, Adedara, Akomolafe, et al, 2020;. In this study, we showed that the administration of CA suppressed ROS and RNS generation by reducing the levels of LPO, XO, and RNS in the testis, hypothalamus, and epididymis of male rats treated with AFB 1 .…”
Section: Sod Dismutase Superoxide Anion Radical (Omentioning
confidence: 66%
See 2 more Smart Citations
“…Moreover, myeloperoxidase (MPO) activity was evaluated according to the previously reported method described by Trush et al, [45,46] using the reaction between O-dianisidine and hydrogen peroxide and absorbance measured spectrophotometrically. MPO catalyzes the oxidation of O-dianisidine, with H 2 O 2 serving as an oxidizing agent, to give a brown-colored oxidized O-dianisidine product, with characteristic absorbance at 460 nm.…”
Section: Assay Of Proinflammatory Biomarkers and Caspase 3 Activitymentioning
confidence: 99%